PENGARUH PEMBERIAN KOMPRES JAHE MERAH (ZINGIBER OFFICIANALE VAR. RUBRUM) TERHADAP NYERI SENDI PADA LANSIA DENGAN HIPERURISEMIA - Vivi Riska Yani Gea; Rostime Hermayerni Simanullang (Universitas Murni Teguh, 2026)
Hyperuricemia in the elderly often causes joint pain that can interfere with daily activities. In addition to pharmacological therapy, joint pain can also be managed using non-pharmacological therapy, one of which is red ginger compress therapy. This study aimed to determine the effect of red ginger compress therapy on reducing joint pain in elderly patients with hyperuricemia at Kedai Durian Public Health Center, Medan Johor District, Medan City. This study employed a pre-experimental design with a one-group pretest–posttest design. The sample consisted of 20 elderly respondents selected using total sampling technique. Joint pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a decrease in joint pain intensity after the administration of red ginger compress therapy, with a p-value < 0.05, indicating a statistically significant difference between pretest and posttest. In conclusion, red ginger compress therapy has a significant effect on reducing joint pain in elderly patients with hyperuricemia. It is recommended that future research involve a larger number of respondents, a longer research duration, and take into account other factors such as diet and physical activity levels.